Raised in newness of life: Religionless Christianity and the sacraments in Bonhoeffer’s baptismal letter to Dietrich Bethge - Dodson, Chris (Stellenbosch Theological Journal, 2023)
In the last days of World War II, Dietrich Bonhoeffer struggled to understand how the church was meant to live faithful to Christ in this catastrophic setting. In a letter written for his godson’s baptism, he connects themes of religionlessness and the sacraments – in particular, baptism, confession, and the Eucharist – to explore what this faithfulness might look like. In five reflections, Bonhoeffer considers and the legacy of Germany and his generation and confesses their sins and failures in hopes of creating an opportunity for the coming generation to begin their life of faith with a religionless disposition more fitting to the time and the calling of Christ. Concluding with examples of how some in subsequent generations have lived in a manner reflective of Bonhoeffer’s hopes, this article asserts that Bonhoeffer’s vision of a life transformed through reception of the sacraments remains a compelling and honest vision for Christian fidelity to both God and the Christian’s worldly context.